(untitled) (Herald of Journalism, 2020)
Discourse got to all types of institutional and everyday communica tion. However television discourse remains an insufficiently known area. Research actuality consists in insufficient studied of genre specific. The variety of genres reflects the real picture of what be going on modern television interactive processes. The author of the article offered the clas sification of new genres of television discourse.